(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2021)
Purpose: The main purpose of this study is to investigate the mediating role of work engagement (WE) in the relationship between perceived organizational support (POS) and turnover intention (TI). Methodology: In this context, to test the model and hypotheses, research data were collected using a survey method from 427 public employees working in the healthcare sector in Erzincan province of Turkey. The data were analyzed using SPSS and AMOS programs. Results: As a result of the analyses, it was found that perceived organizational support has a positive effect on work engagement and a negative effect on turnover intention, and work engagement and turnover intention variables are negatively correlated. It was also concluded that there was a partial mediating role of work engagement in the relationship between perceived organizational support and turnover intention. Conclusion: In this study, it was determined that WE has a partial intermediary role in the relationship between POS and TI. According to these findings, the support provided to the employee by the organization reduces employee intention to quit. In this context, when organizational management implements practices that will ensure employee commitment in addition to supporting employees and creating this perception, it can further reduce the intention of employees to quit.